Preparation method and application of graphene and TiO2 composite resin

Through the preparation of graphene and TiO2 composite resin, the problem of low efficiency and secondary pollution in the treatment of low-concentration organic pollutants is solved, efficient catalytic degradation and continuous use of materials are achieved, and the recycling process is simplified.

CN119140073APending Publication Date: 2024-12-17JIANGSU GUOCHUANG ENVIRO PROTECTION TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411574094.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing TiO2 photocatalytic technology is inefficient when dealing with low-concentration and strongly hydrophobic organic pollutants, and is prone to secondary pollution, and it is difficult to recover nano powders, which affects practical application.

Method used

Using the preparation method of graphene and TiO2 composite resin, the preparation of lipophilic TiO2 nanoparticles and graphene/TiO2 composites is improved by combining the adsorption/catalytic synergy function to improve catalytic activity and realize the continuous use of materials.

Benefits of technology

It improves the catalytic activity and degradation efficiency of TiO2, avoids secondary pollution, simplifies the separation and recovery of materials, and is suitable for the adsorption and catalytic degradation of organic matter in water and gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119140073A_ABST
    Figure CN119140073A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of graphene and TiO2 composite resin, and belongs to the technical field of photocatalytic composite materials. According to the technical scheme, the preparation method of the graphene and TiO2 composite resin is characterized by comprising the following steps: S1, preparing oleophylic TiO2 nanoparticles; s2, preparing a graphene / TiO2 compound; s3, preparing an oil phase solution, namely dissolving the graphene / TiO2 compound prepared in S2 into a pore-foaming agent, respectively adding a monomer and an initiator, and uniformly mixing under an ice bath condition; s4, synthesizing graphene and TiO2 composite resin with an adsorption / catalysis synergistic function; intermediate products generated in the photocatalytic reaction process are adsorbed on the surface of the adsorbent, so that degradation intermediates can be completely degraded into CO2, water and other inorganic matters without leaving the surfaces of catalyst particles in time, and the problem of secondary pollution possibly generated by the degradation intermediates is avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic composite materials, and in particular to a preparation method and application of a graphene and TiO2 composite resin. Background Art

[0002] After decades of development, photocatalytic technology has made great progress in environmental pollution control and energy fields. However, there are still some key scientific problems in the treatment of environmental pollutants with TiO2 semiconductor-based photocatalytic technology, which seriously hinders its practical application. TiO2 photocatalysis is a new green environmental pollution treatment technology with obvious degradation effect on a variety of organic matter and has broad application prospects.

[0003] There are several ways to improve the photocatalytic activity of TiO2: 1) The earliest TiO2 studied was nanopowder, which has a large contact surface area and good photocatalytic degradation effect, but it is not conducive to the recovery of the catalyst and is prone to loss and waste. In addition, nanopowders are prone to agglomeration and inactivation at high concentrations, which limits their practical applications. Studies have shown that nano-TiO2 remaining in environmental media may have potential cytotoxicity to organisms.

[0004] 2) The recombination rate of photogenerated electrons and holes in the bulk or surface of TiO2 is high, and the quantum efficiency is low, less than 10%, which makes TiO2 not only expensive for sewage treatment, but also has a slow degradation rate.

[0005] 3) The band gap width of anatase TiO2 semiconductor is 3.2eV, and its corresponding absorption wavelength is 387nm. It can only absorb ultraviolet light with a wavelength below 387nm, and has a narrow light response range. This part of ultraviolet light accounts for less than 4%-5% of sunlight, so the utilization efficiency of solar energy is only about 1%. Therefore, the general light source for photocatalysis is ultraviolet lamp, which has a high degradation cost, seriously limiting its practical application.

[0006] TiO2 photocatalytic degradation of organic pollutants belongs to heterogeneous catalysis, and its catalytic reaction inevitably involves the mass transfer process of organic pollutants. However, the specific surface area of ​​TiO2 photocatalyst is limited, and due to the presence of a large number of surface hydroxyl groups, the main surface is hydrophilic under the action of ultraviolet light, and it has basically no adsorption capacity for non-polar (hydrophobic) organic pollutants. A large number of studies have shown that the oxidation of organic matter by hydroxyl radicals generated on the TiO2 surface is the key to photocatalytic degradation. Therefore, the adsorption of organic matter on the TiO2 surface is the rate-controlling step that determines the photocatalytic degradation kinetics. When TiO2 is used to treat low-concentration, highly hydrophobic environmental pollutants in the environment, the photocatalytic degradation efficiency is low and it is difficult to achieve satisfactory results.

[0007] When TiO2 degrades pollutants, it is mainly through the redox reaction of hydroxyl radicals produced by the action of light and TiO2 with toxic organic pollutants. This free radical reaction is not selective in degrading pollutants. When several organic pollutants coexist, it preferentially catalyzes the degradation of high-concentration pollutants adsorbed on its surface, mainly hydrophilic organic compounds, while low-concentration strongly hydrophobic organic pollutants cannot be effectively degraded due to small adsorption amounts or almost no adsorption.

[0008] So far, the commonly used method to improve catalytic activity is to improve the photocatalytic activity by controlling the morphology (spherical, rod-shaped, fibrous, tubular or flake-shaped), size, specific surface area, pore volume, pore structure, crystal phase or the proportion of high active surfaces of TiO2; it can also be achieved through metal ion or non-metal doping, precious metal deposition, composite semiconductors, dye photosensitization and preparation of composite photocatalysts with adsorption / photocatalytic synergistic functions.

[0009] The preparation of composite materials with synergistic adsorption / photocatalysis is also an effective method for removing organic pollutants. Although element doping, precious metal deposition, semiconductor composite and dye photosensitization can greatly improve the catalytic activity of TiO2, or extend the response of TiO2 to light to the visible light region, when TiO2 is used to treat low-concentration, highly hydrophobic and highly toxic organic pollutants, the photocatalytic degradation efficiency is low, and degradation intermediates are often generated, which may cause secondary pollution problems. For example, when pure TiO2 is used to photocatalytically degrade pentachlorophenol, more toxic dioxin-like compounds may be produced, causing greater pollution.

[0010] Because these modified TiO2 materials have limited specific surface area and a large number of surface hydroxyl groups, they have little adsorption capacity for non-polar (hydrophobic) organic pollutants. However, a large number of studies have shown that the oxidation of organic matter by hydroxyl radicals generated on the TiO2 surface is the first step in photocatalytic degradation. Therefore, the adsorption of organic matter on the TiO2 surface is one of the key factors determining the kinetics of photocatalytic degradation. Therefore, it is necessary to seek new materials for improvement. Summary of the invention

[0011] In view of the problems mentioned in the background technology, the purpose of the present invention is to provide a preparation method and application of a graphene and TiO2 composite resin to solve the problems mentioned in the background technology.

[0012] The above technical objectives of the present invention are achieved through the following technical solutions: A method for preparing a graphene and TiO2 composite resin comprises the following steps: S1, preparing oleophilic TiO2 nanoparticles; S2, preparing graphene / TiO2 composite; S3, preparing an oil phase solution: dissolving the graphene / TiO2 composite prepared in S2 in a porogen, adding a monomer and an initiator respectively, and mixing them evenly in an ice bath; S4. Synthesis of graphene and TiO2 composite resin with adsorption / catalytic synergistic function: add emulsifier and dispersant to the aqueous solution, ultrasonically stir evenly, add the oil phase solution prepared in S3 to the solution, heat and stir evenly at low temperature, then heat to react, and then precipitate, filter, wash and dry the solution after the reaction to finally obtain a graphene and TiO2 composite resin with adsorption / catalytic synergistic function.

[0013] Preferably, the mass ratio of graphene:TiO2:resin is 1:(1-5):(10-50).

[0014] Preferably, the preparation process of the lipophilic TiO2 nanoparticles is: mix an appropriate amount of TiO2 powder with water, stir with a glass rod, add a certain amount of wetting dispersant after mixing evenly, place in an ultrasonic cleaner for a certain period of time, then rinse with ethanol 3 times, and dry in an electric blast drying oven to obtain TiO2 powder after lipophilic treatment.

[0015] Preferably, the preparation process of the graphene / TiO2 composite is as follows: graphene and TiO2 powder are added to deionized water in a certain proportion, uniformly dispersed by ultrasonication, and then the volume is fixed to 45 mL, placed in a 50 mL hydrothermal autoclave and treated at 160°C for 24 hours, with a filling degree of 90%, and the composite after the hydrothermal reaction is washed with ethanol and vacuum dried to obtain the graphene / TiO2 composite powder.

[0016] Preferably, the stirring rate in S4 is 100-1500 rpm, the stirring time is 12-80 h, and the stirring reaction temperature is 60-95°C.

[0017] Preferably, the mass of the N-vinyl pyrrolidone accounts for 10-90% of the total mass of N-vinyl pyrrolidone and divinylbenzene.

[0018] Preferably, the initiator is azo or benzoyl; the porogen is one or more of methanol, toluene, cyclohexanol, DMF, and DMSO; the emulsifier is an anionic surfactant; and the dispersant is one or more of PVP, HEC, and PEG.

[0019] Preferably, the composite resin has an average particle size of 2-100 µm, a magnetization intensity of 5-19.5 emu / g, and a specific surface area of ​​210-950 m2 / g.

[0020] Preferably, the emulsifier added to the aqueous solution in S4 accounts for 0.5%-0.8% of the water mass, and the dispersant accounts for 0.8%-1% of the water mass.

[0021] The invention also discloses an application of a graphene and TiO2 composite resin, and the prepared graphene and TiO2 composite resin is applied to the adsorption and catalytic degradation of organic matter in water and gas.

[0022] In summary, the present invention mainly has the following beneficial effects: 1. The effect of adsorbent can be used to enrich and concentrate low-concentration organic pollutants in the pores or on the surface of the adsorbent, promote the migration of organic pollutants to the adsorbent, and then transfer to the catalyst surface, thereby greatly improving the degradation efficiency of TiO2.

[0023] 2. The TiO2 component in the composite photocatalyst is used to degrade organic pollutants adsorbed on the surface of the adsorbent, which can regenerate the adsorbent, thereby realizing the continuous use of the material and avoiding secondary pollution caused by desorption of the adsorbent due to saturated adsorption.

[0024] 3. The intermediate products produced during the photocatalytic reaction are adsorbed on the surface of the adsorbent, so that the degradation intermediates are completely degraded into CO2, water and other inorganic substances before they can leave the surface of the catalyst particles, thus avoiding the secondary pollution problem that may be caused by the degradation intermediates.

[0025] 4. The adsorbent can interact with the catalyst to accelerate the separation of electron-hole pairs, thereby improving the catalytic activity of the photocatalyst and achieving good separation of the photogenerated electron-hole pairs produced by TiO2, thereby greatly improving the catalytic activity of TiO2.

[0026] 5. Conventional nano-powder photocatalysis often has problems such as difficult separation and recovery, easy agglomeration and inactivation, which limits its practical application. The composite of adsorbent and photocatalyst can greatly reduce the agglomeration of TiO2, and separation and recovery are easier than powdered TiO2. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 It is a schematic diagram of the self-made continuous flow analysis equipment of the present invention when conducting experiments; Figure 2 This is a graph showing the effect of flow rate on photocatalytic degradation efficiency during the experiment of the present invention; Figure 3 This is a diagram showing the effect of temperature on photocatalytic degradation efficiency during the experiment of the present invention; Figure 4 It is a photocatalytic degradation curve diagram of aminoacetic acid solution at different initial concentrations during the experiment of the present invention; Figure 5 It is a flow chart of the present invention. DETAILED DESCRIPTION

[0028] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0029] A method for preparing a graphene and TiO2 composite resin comprises the following steps: S1, preparing oleophilic TiO2 nanoparticles; S2, preparing graphene / TiO2 composite; S3, preparing an oil phase solution: dissolving the graphene / TiO2 composite prepared in S2 in a porogen, adding a monomer and an initiator respectively, and mixing them evenly in an ice bath; S4. Synthesis of graphene and TiO2 composite resin with adsorption / catalytic synergistic function: add emulsifier and dispersant to the aqueous solution, ultrasonically stir evenly, add the oil phase solution prepared in S3 to the solution, heat and stir evenly at low temperature, then heat to react, and then precipitate, filter, wash and dry the solution after the reaction to finally obtain a graphene and TiO2 composite resin with adsorption / catalytic synergistic function.

[0030] Among them, the mass ratio of graphene:TiO2:resin is 1:2:13.

[0031] Among them, the preparation process of lipophilic TiO2 nanoparticles is: mix an appropriate amount of TiO2 powder with water, stir with a glass rod, add a certain amount of wetting dispersant after mixing evenly, place it in an ultrasonic cleaner for a certain period of time, then rinse with ethanol 3 times, and dry it in an electric blast drying oven to obtain TiO2 powder after lipophilic treatment.

[0032] Among them, the preparation process of graphene / TiO2 composite is as follows: add graphene and TiO2 powder in a certain proportion to deionized water, disperse them evenly by ultrasonication, adjust the volume to 45 mL, put them into a 50 mL hydrothermal autoclave and treat them at 160°C for 24 hours, the filling degree is 90%, wash the composite after the hydrothermal reaction with ethanol, and vacuum dry it to obtain the graphene / TiO2 composite powder.

[0033] Wherein, the stirring rate in S4 is: 100 rpm, the stirring time is: 2 h, and the stirring reaction temperature is 65°C.

[0034] Among them, the mass of N-vinyl pyrrolidone accounts for 10% of the total mass of N-vinyl pyrrolidone and divinylbenzene.

[0035] Among them, the initiator is azo or benzoyl; the porogen is methanol; the emulsifier is an anionic surfactant; and the dispersant is PVP.

[0036] The average particle size of the composite resin is 15 µm and the specific surface area is 230 m 2 / g.

[0037] Among them, the emulsifier added to the aqueous solution in S4 accounts for 0.5% of the water mass, and the dispersant accounts for 0.8% of the water mass. Example

[0038] A method for preparing a graphene and TiO2 composite resin comprises the following steps: S1, preparing oleophilic TiO2 nanoparticles; S2, preparing graphene / TiO2 composite; S3, preparing an oil phase solution: dissolving the graphene / TiO2 composite prepared in S2 in a porogen, adding a monomer and an initiator respectively, and mixing them evenly in an ice bath; S4. Synthesis of graphene and TiO2 composite resin with adsorption / catalytic synergistic function: add emulsifier and dispersant to the aqueous solution, ultrasonically stir evenly, add the oil phase solution prepared in S3 to the solution, heat and stir evenly at low temperature, then heat to react, and then precipitate, filter, wash and dry the solution after the reaction to finally obtain a graphene and TiO2 composite resin with adsorption / catalytic synergistic function.

[0039] Among them, the mass ratio of graphene:TiO2:resin is 1:5:50.

[0040] Among them, the preparation process of lipophilic TiO2 nanoparticles is: mix an appropriate amount of TiO2 powder with water, stir with a glass rod, add a certain amount of wetting dispersant after mixing evenly, place it in an ultrasonic cleaner for a certain period of time, then rinse with ethanol 3 times, and dry it in an electric blast drying oven to obtain TiO2 powder after lipophilic treatment.

[0041] Among them, the preparation process of graphene / TiO2 composite is as follows: add graphene and TiO2 powder in a certain proportion to deionized water, disperse them evenly by ultrasonication, adjust the volume to 45 mL, put them into a 50 mL hydrothermal autoclave and treat them at 160°C for 24 hours, the filling degree is 90%, wash the composite after the hydrothermal reaction with ethanol, and vacuum dry it to obtain the graphene / TiO2 composite powder.

[0042] Among them, the stirring rate in S4 is: 1500 rpm, the stirring time is: 80 h, and the stirring reaction temperature is 95°C.

[0043] The mass of N-vinyl pyrrolidone accounts for 10-90% of the total mass of N-vinyl pyrrolidone and divinylbenzene.

[0044] The initiator is azo or benzoyl; the porogen is toluene; the emulsifier is an anionic surfactant; and the dispersant is PEG.

[0045] The average particle size of the composite resin is 100 µm and the specific surface area is 950 m 2 / g.

[0046] Among them, the emulsifier added to the aqueous solution in S4 accounts for 0.8% of the water mass, and the dispersant accounts for 1% of the water mass. Example

[0047] A method for preparing a graphene and TiO2 composite resin comprises the following steps: S1, preparing oleophilic TiO2 nanoparticles; S2, preparing graphene / TiO2 composite; S3, preparing an oil phase solution: dissolving the graphene / TiO2 composite prepared in S2 in a porogen, adding a monomer and an initiator respectively, and mixing them evenly in an ice bath; S4. Synthesis of graphene and TiO2 composite resin with adsorption / catalytic synergistic function: add emulsifier and dispersant to the aqueous solution, ultrasonically stir evenly, add the oil phase solution prepared in S3 to the solution, heat and stir evenly at low temperature, then heat to react, and then precipitate, filter, wash and dry the solution after the reaction to finally obtain a graphene and TiO2 composite resin with adsorption / catalytic synergistic function.

[0048] Among them, the mass ratio of graphene:TiO2:resin is 1:4:30.

[0049] Among them, the preparation process of lipophilic TiO2 nanoparticles is: mix an appropriate amount of TiO2 powder with water, stir with a glass rod, add a certain amount of wetting dispersant after mixing evenly, place it in an ultrasonic cleaner for a certain period of time, then rinse with ethanol 3 times, and dry it in an electric blast drying oven to obtain TiO2 powder after lipophilic treatment.

[0050] Among them, the preparation process of graphene / TiO2 composite is as follows: add graphene and TiO2 powder in a certain proportion to deionized water, disperse them evenly by ultrasonication, adjust the volume to 45 mL, put them into a 50 mL hydrothermal autoclave and treat them at 160°C for 24 hours, the filling degree is 90%, wash the composite after the hydrothermal reaction with ethanol, and vacuum dry it to obtain the graphene / TiO2 composite powder.

[0051] Among them, the stirring rate in S4 is: 800 rpm, the stirring time is: 60 h, and the stirring reaction temperature is 75°C.

[0052] The mass of N-vinyl pyrrolidone accounts for 10-90% of the total mass of N-vinyl pyrrolidone and divinylbenzene.

[0053] The initiator is azo or benzoyl; the porogen is cyclohexanol; the emulsifier is an anionic surfactant; and the dispersant is PVP.

[0054] The average particle size of the composite resin is 50 µm and the specific surface area is 210 m 2 / g.

[0055] Among them, the emulsifier added to the aqueous solution in S4 accounts for 0.7% of the water mass, and the dispersant accounts for 0.9% of the water mass.

[0056] refer to Figures 1 to 4 , a method for preparing a graphene and TiO2 composite resin, comprising the following steps: S1, preparing oleophilic TiO2 nanoparticles; S2, preparing graphene / TiO2 composite; S3, preparing an oil phase solution: dissolving the graphene / TiO2 composite prepared in S2 in a porogen, adding a monomer and an initiator respectively, and mixing them evenly in an ice bath; S4. Synthesis of graphene and TiO2 composite resin with adsorption / catalytic synergistic function: add emulsifier and dispersant to the aqueous solution, ultrasonically stir evenly, add the oil phase solution prepared in S3 to the solution, heat and stir evenly at low temperature, then heat to react, and then precipitate, filter, wash and dry the solution after the reaction to finally obtain a graphene and TiO2 composite resin with adsorption / catalytic synergistic function.

[0057] Among them, the mass ratio of graphene:TiO2:resin is 1:2.6:28.

[0058] Among them, the preparation process of graphene / TiO2 composite is as follows: add graphene and TiO2 powder in a certain proportion to deionized water, disperse them evenly by ultrasonication, adjust the volume to 45 mL, put them into a 50 mL hydrothermal autoclave and treat them at 160°C for 24 hours, the filling degree is 90%, wash the composite after the hydrothermal reaction with ethanol, and vacuum dry it to obtain the graphene / TiO2 composite powder.

[0059] refer to Figures 1 to 5 In order to verify the superiority of the present invention, the performance of the graphene and TiO2 composite resin prepared by the present invention was prepared, and the following experiments were carried out to obtain the following experimental results: Experimental part: Experimental materials and reagents: Ferric chloride hexahydrate (FeCl3·6H2O), tetrabutyl titanate (TBT) and 2-aminoterephthalic acid (H2ATA) were purchased from TCI (Shanghai) Chemical Industry Development Co., Ltd. Sulfonamide, NEDD, sodium dodecyl sulfate, hydrazine sulfate, zinc sulfate, copper sulfate pentahydrate, methanol (MeOH), tert-butyl alcohol (TBA), N,N-dimethylformamide (DMF) and hydrogen peroxide (H2O2, 30% w / w) were purchased from Sinopharm Chemical Reagent Co., Ltd. Potassium persulfate, sodium hydroxide, borax and disodium ethylenediaminetetraacetate (EDTA) were purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0060] 1 000 mg / L total nitrogen standard stock solution: Dissolve 7.218 g of high-grade pure potassium nitrate dried at (105±5)℃ to constant weight in water, dilute to 1 000 mL and mix well. 10 mg / L total nitrogen standard working solution: Dissolve 1 mL of total nitrogen standard stock solution in water to 100 mL. 1 000 mg / L aminoacetic acid standard stock solution: Dissolve 5.360 g in water, transfer to a 1 000 mL volumetric flask and dilute to 1 000 mL and mix well. 10 mg / L aminoacetic acid standard working solution: Dissolve 1 mL of aminoacetic acid standard stock solution in water to 100 mL.

[0061] Instruments and equipment, including the laboratory-made continuous flow analysis equipment shown in Figure 1.

[0062] The experimental method is as follows: The new TiO2 composite photocatalytic material is attached to the inner wall of the photocatalytic degradation unit pipeline of the continuous flow analysis equipment by high-temperature sintering process, and the detection method is developed and the instrument performance is verified. 0.00, 0.20, 0.50, 1.00, 2.00, and 5.00 mL of 10 mg / L total nitrogen standard solution are measured into a 10 mL volumetric flask, and the volume is adjusted to the scale line with ultrapure water. The absorbance is measured in turn by the total nitrogen continuous flow analyzer, and the calibration curve is drawn with the absorbance as the ordinate and the total nitrogen concentration as the abscissa. The aminoacetic acid standard solution and the total nitrogen standard solution are measured in parallel under different conditions, and the photocatalytic degradation efficiency is calculated according to the following formula: (R): R= P1 / P2 ×100%, where R is the photocatalytic degradation efficiency, %; P1 is the measurement result of the aminoacetic acid standard solution, mg / L; P2 is the measurement result of the total nitrogen standard solution, mg / L; The experimental results are as follows, wherein each item of the experimental results is the average value of the results of Example 1, Example 2 and Example 3 as the experimental result: Effect of injection flow rate: Using 1 mg / L aminoacetic acid solution, the temperature was set to 100 °C, and the flow rate was changed to 0.2, 0.5, 0.8, 1.1, 1.4, 1.7, 2.0, 2.3, 2.6, 2.9, 3.2 mL / min by adjusting the peristaltic pump of the flow analyzer. The photocatalytic degradation efficiency of aminoacetic acid at different injection flow rates was measured in parallel. The specific results are shown in Figure 2. When the flow rate is controlled within 3 mL / min, the photocatalytic degradation efficiency can reach more than 98%; the specific data can be seen in Figure 2. Figure 2 .

[0063] Effect of temperature: Using 1 mg / L aminoacetic acid solution, the flow rate was set to 2.5 mL / min, and the heating temperature of the photocatalytic degradation unit was set to 50, 60, 70, 75, 80, 85, 90, 95, 100, 105, 110 °C, and the photocatalytic degradation efficiency at different temperatures was measured in parallel. The results are shown in Figure 3. As can be seen from Figure 3, with the increase of temperature, the photocatalytic degradation efficiency gradually increases. When the temperature reaches 85 °C, the photocatalytic degradation efficiency has reached more than 95%; when the temperature reaches 90 °C, the photocatalytic degradation efficiency is close to 100%; the specific data is shown in Figure 3. Figure 3 .

[0064] Effect of initial concentration: The flow rate was set to 2.5 mL / min, the photocatalytic temperature was set to 90 °C, and the photocatalytic digestion experiment was carried out with aminoacetic acid solutions with initial concentrations (PO ) of 0.50, 1.00, 1.50, 2.50, and 5.00 mg / L, respectively. The photocatalytic degradation curves of aminoacetic acid solutions at different initial concentrations were plotted, as shown in Figure 4. As can be seen from Figure 4, the photocatalytic degradation efficiency gradually increases with the extension of time. The low-concentration sample can reach a photocatalytic degradation efficiency of more than 95% within 4 minutes. As the concentration of the solution increases, the photocatalytic degradation time is gradually extended. When the concentration reaches 5.00 mg / L, the sample can reach a photocatalytic degradation efficiency of more than 95% in 5.5 minutes, which is in line with the Langmuir-Hinshelwood model; for specific data, see Figure 4 .

[0065] Determination of total nitrogen in actual water bodies: Surface water samples from the Taihu Lake Basin were collected and the total nitrogen concentration was determined using the manual method HJ 636-2012 and the flow analyzer. The relative deviation of the two methods was calculated and the results are shown in Figure 5 The results of the 36 water quality total nitrogen test using the manual method and flow analysis method were consistent, with relative deviations within 5%, meeting the quality control requirements of the water quality testing laboratory.

[0066] In a comprehensive analysis, the graphene and TiO2 composite resin prepared by the present invention has been verified and applied in the continuous flow analysis of total nitrogen in water quality. The effects of sample concentration, photocatalytic temperature and photocatalytic time on catalytic efficiency are optimized, which not only has high catalytic degradation efficiency, but also has good stability and high accuracy. The test results are well consistent with the national standard manual method HJ 636-2012, and can be widely used in the total nitrogen detection of different types of water quality, which fully reflects the superiority of the present invention.

[0067] From the above experiments, it can be found that the experimental average results of Example 1, Example 2 and Example 3 of the present invention are respectively affected by the injection flow rate, the temperature and the initial concentration. In addition, Example 1, Example 2 and Example 3 of the present invention are also superior to traditional TiO2 photocatalytic materials.

[0068] In order to verify the superiority of the present invention, nano titanium dioxide produced by Nanjing Baoket New Materials Co., Ltd. was selected for experiment, and the experimental results of Examples 1 / 2 / 3 were homogenized with the experimental results of the comparative document (nano titanium dioxide produced by Nanjing Baoket New Materials Co., Ltd.), and the following data results were obtained:

[0069] It can be found from the above table that the present invention is superior in various performances compared with the reference document.

[0070] The effect of adsorbent can be used to enrich and concentrate low-concentration organic pollutants in the pores or on the surface of the adsorbent, promote the migration of organic pollutants to the adsorbent, and then transfer to the catalyst surface, thereby greatly improving the degradation efficiency of TiO2. The TiO2 component in the composite photocatalyst is used to degrade organic pollutants adsorbed on the surface of the adsorbent, which can regenerate the adsorbent, thereby realizing the continuous use of the material and avoiding the secondary pollution caused by the desorption of the adsorbent due to saturated adsorption. The intermediates produced during the photocatalytic reaction are adsorbed on the surface of the adsorbent, so that the degradation intermediates are completely degraded into CO2, water and other inorganic substances before they can leave the surface of the catalyst particles, avoiding the secondary pollution problem that may be caused by the degradation intermediates. The adsorbent can interact with the catalyst to accelerate the separation of electron-hole pairs, thereby improving the catalytic activity of the photocatalyst and achieving a good separation of the photogenerated electron-hole pairs produced by TiO2, thereby greatly improving the catalytic activity of TiO2. Conventional nanopowder photocatalysis often has problems such as difficult separation and recovery, and easy agglomeration and inactivation, which limits its practical application. The composite of adsorbent and photocatalyst can greatly reduce the agglomeration of TiO2, and separation and recovery are easier than powdered TiO2.

[0071] Photocatalysts can use light energy to degrade environmental pollutants, which not only plays a role in environmental governance, but also saves energy. Among them, TiO_2 is a traditional photocatalytic material. Due to its advantages such as low price, non-toxicity, and stable chemical properties, pure phase TiO_2 can only absorb ultraviolet light and cannot use visible light for photocatalytic degradation, which limits its application. Researchers have conducted modification research on it and achieved certain results, but it still needs further improvement to make it not only have excellent performance, but also have more practical application value.

[0072] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a graphene and TiO2 composite resin, characterized in that: The following steps are involved: S1, preparing oleophilic TiO2 nanoparticles; S2, preparing graphene / TiO2 composite; S3, preparing an oil phase solution: dissolving the graphene / TiO2 composite prepared in S2 in a porogen, adding a monomer and an initiator respectively, and mixing them evenly in an ice bath; S4. Synthesis of graphene and TiO2 composite resin with adsorption / catalytic synergistic function: add emulsifier and dispersant to the aqueous solution, ultrasonically stir evenly, add the oil phase solution prepared in S3 to the solution, heat and stir evenly at low temperature, then heat to react, and then precipitate, filter, wash and dry the solution after the reaction to finally obtain a graphene and TiO2 composite resin with adsorption / catalytic synergistic function.

2. The method for preparing a graphene and TiO2 composite resin according to claim 1, characterized in that: The mass ratio of graphene:TiO2:resin is 1:(1-5):(10-50).

3. The method for preparing a graphene and TiO2 composite resin according to claim 1, characterized in that: The preparation process of the lipophilic TiO2 nanoparticles is as follows: mix an appropriate amount of TiO2 powder with water, stir with a glass rod, add a certain amount of wetting dispersant after mixing evenly, place in an ultrasonic cleaner for a certain period of time, then rinse with ethanol three times, and dry in an electric blast drying oven to obtain TiO2 powder after lipophilic treatment.

4. The method for preparing a graphene and TiO2 composite resin according to claim 1, characterized in that: The preparation process of the graphene / TiO2 composite is as follows: graphene and TiO2 powder are added into deionized water in a certain proportion, uniformly dispersed by ultrasonication, and then fixed to 45 mL, and then placed in a 50 mL hydrothermal autoclave for treatment at 160° C. for 24 h, with a filling degree of 90%. After the composite after the hydrothermal reaction is washed with ethanol, it is vacuum dried to obtain the graphene / TiO2 composite powder.

5. The method for preparing a graphene and TiO2 composite resin according to claim 1, characterized in that: In the S4, the stirring rate is 100-1500 rpm, the stirring time is 12-80 h, and the stirring reaction temperature is 60-95°C.

6. The method for preparing a graphene and TiO2 composite resin according to claim 1, characterized in that: The mass of the N-vinyl pyrrolidone accounts for 10-90% of the total mass of N-vinyl pyrrolidone and divinylbenzene.

7. The method for preparing a graphene and TiO2 composite resin according to claim 1, characterized in that: The initiator is azo or benzoyl; the porogen is one or more of methanol, toluene, cyclohexanol, DMF, and DMSO; the emulsifier is an anionic surfactant; and the dispersant is one or more of PVP, HEC, and PEG.

8. The method for preparing a graphene and TiO2 composite resin according to claim 1, characterized in that: The composite resin has an average particle size of 2-100 μm and a specific surface area of ​​210-950 m 2 / g.

9. The method for preparing a graphene and TiO2 composite resin according to claim 1, characterized in that: In the S4, the emulsifier added to the aqueous solution accounts for 0.5%-0.8% of the water mass, and the dispersant accounts for 0.8%-1% of the water mass.

10. An application of a graphene and TiO2 composite resin, characterized in that: The graphene and TiO2 composite resin prepared according to any one of claims 1 to 9 is applied to the adsorption and catalytic degradation of organic matter in water and gas.